The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s40359-022-00992-5
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in pre-dialysis patients with chronic kidney disease: the role of Big-Five personality traits and illness denial

Abstract: Background Health-Related Quality of Life (HRQoL) in patients with chronic kidney disease (CKD) is significantly affected, regardless of the stage of the disease, as regards the physical, psychological and social functioning dimension. Big-Five personality traits can affect patients’ HRQoL and willingness to take treatment options. Illness denial consists of denial of negative emotions, resistance to change and conscious avoidance. Poorer HRQoL can predict a higher risk of hospitalization and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Similarly, in a study with end-stage renal disease patients, Fricchione et al [126] showed that those with low levels of illness denial were more sensitive, had more anxiety and depression, and also reported greater sleep disturbances than patients with high levels of illness denial. In a more recent study involving pre-dialysis patients with chronic kidney disease, Pugi et al [127] found that illness denial was a significant predictor of higher levels of health-related quality of life. The authors showed that chronic kidney disease patients with illness denial were not bothered by the effects of the kidney disease on daily life, did not perceive high levels of frustration and interference of kidney disease in their life, did not report any concentration problems or mental confusion [127].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Similarly, in a study with end-stage renal disease patients, Fricchione et al [126] showed that those with low levels of illness denial were more sensitive, had more anxiety and depression, and also reported greater sleep disturbances than patients with high levels of illness denial. In a more recent study involving pre-dialysis patients with chronic kidney disease, Pugi et al [127] found that illness denial was a significant predictor of higher levels of health-related quality of life. The authors showed that chronic kidney disease patients with illness denial were not bothered by the effects of the kidney disease on daily life, did not perceive high levels of frustration and interference of kidney disease in their life, did not report any concentration problems or mental confusion [127].…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent study involving pre-dialysis patients with chronic kidney disease, Pugi et al [127] found that illness denial was a significant predictor of higher levels of health-related quality of life. The authors showed that chronic kidney disease patients with illness denial were not bothered by the effects of the kidney disease on daily life, did not perceive high levels of frustration and interference of kidney disease in their life, did not report any concentration problems or mental confusion [127]. In a cross-sectional investigation involving hemodialysis patients, however, Carvalho et al [128] showed that illness denial was associated with impaired health-related quality of life.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations